Research on The Wireless Communication Scheme of Substation Full Coverage. Issue 5 (January 2021) - Zhang, Hongmei; Zhang, Ji; Zheng, Ziyao; Li, Liangyu; Zhang, Yan
Abstract: In order to meet the mobility and Broadband communication requirements of smart substation, this paper proposes a wireless communication scheme based on Wireless-Fidelity network for substation all-domain coverage, and makes an in-depth analysis of network performance. In this way, a communication scheme suitable for specific electric power application scenarios can be created, which can effectively improve the basic support capacity of information communication.